Where Do Indian Institutes Fall Short with Respect to World Class Institutes? "Gap Analysis" - Naik, B. M. (Journal of Engineering Education Transformations, 2015)
Indian institutes do not stand high in the world list of educational institutions. Thousands of students every year go abroad for higher education. Foreign universities have started coming into India. Universities in India are being blamed for producing unemployable graduates. UGC (University Grants Commission) in India appears to have failed in its mandated mission. A committee appointed by MHRD (Ministry of Human Resource and Development), Government of India, under the chairmanship of Mr. Hari Gautamrecommended that UGC be abolished. Higher and technical education is behind the needs of themodem times, adversely affecting economic and social growth in India. Both the President and Prime Minister of India have been publicly expressing concern on this account for many years. Yet no improvement is noticed. Some Chinese universities on the other hand have shot up from very low ranking to 35 in the world. Are the words of President and Prime Minister falling on deaf ears? Are they merely speaking like parrots from year to year? Indian institutes are insensitive and woefully unsuited to global demands and are too far behind the world. Do we need to dream big, think great and show commitment to improve? It is said that those who dream big perform better; dreams give energy to minds, mobilize resources and make people competitive and ambitious. The presence of world class institutions is a differentiating factor between the developed and the developing world. They produce globally competent leaders with high intellectual capability so badly needed to raise a nation to greater heights. They produce intellectual capital so essential for the welfare of people. Regions, nations and cities, even if endowed with abundant natural resources like minerals, land, water,etc., are not prosperous if they do not have world class higher education institutes. Knowledge institutions are like "Light Houses" to society. They are reference points providing guidance and giving direction to people and industry in stormy changes. This is an age of technology, in which scientific and technological capabilities matter most. Making the institutions world class is not an option but a compulsion. It is now not only a matter of spending more money, appointing more men, or providing infrastructure. It is more a matter of adopting appropriate visions and missions and selecting strategies. Indian education system is still traditionbound. Outdated systems like affiliated colleges, lack of autonomy,absence of research and Intellectual Property Rights (IPR), have crippled the education. Investments being made by government are subsidizing only the inefficiencies. This is because they lack a strategic outlook. Indian professors abroad have done wonders. Why cannot they perform wonders in India? Is it because they have to work here in India with poor systems and poor governance? This paper recommends adoption of autonomy, research approach, creation of research parks, commercial exploitation of findings of research, patenting, enabling professors to be globally competitive, increasing mobility of professors, etc. This article presents in brief, the gap analysis in respect of visions and missions, policies and practice, organization structures, systems and procedures in India and their counterpart institutions in developed countries. Transformation of higher and technical education to world class level is critical to nurturing able leaders in various professions and vocations, and in critical to turn people’s well-being.